Information, Production, and the Term Structure - Day, Theodore E. (Journal of Political Economy, 1986)
The difference between the forward rate of interest implicit in the term structure of interest rates and the expected future spot rate is usually referred to as a liquidity premium. This paper examines the determinants of the liquidity premiums implicit in the term structure of real interest rates using a three-date economy with production. The sign of the liquidity premium is characterized in terms of the parameters that describe the uncertainty in the economy. The results suggest that the liquidity premiums implicit in the real term structure of interest rates may sometimes be negative.